Analysis of Factors Associated with The Incidence of Hypertension in Menopausal Women in The Teluk Tiram Health Center Working Area - Ariani, Risna; Noor, Meitira Syahadatina; Sauqi, Hardyan; Illiandri, Oski; Kania, Nia (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
This study analyzes the distribution of characteristics and factors associated with hypertension among menopausal women in the Teluk Tiram Health Center area. Hypertension is a significant health issue affecting postmenopausal women, yet local evidence from community-based health care in Indonesia is limited. A cross-sectional design was used, involving 105 menopausal women. Data collection included structured surveys assessing age at menopause, Body Mass Index (BMI), physical activity, stress levels, sleep quality, and history of hormonal contraceptive use. Bivariate analysis, utilizing chi-square tests, along with multivariate analysis through logistic regression, was conducted to identify associated factors. The findings indicated that early menopause, high BMI, low physical activity, elevated stress levels, poor sleep quality, and a history of combined hormonal contraceptive use were significantly related to hypertension. Multivariate analysis further identified BMI as the most influential factor, succeeded by low physical activity and high stress levels. These results underscore the importance of weight management, promotion of physical activity, and stress reduction strategies to lower the risk of hypertension in menopausal women. Ultimately, this research emphasizes the multifactorial nature of hypertension during menopause and calls for comprehensive prevention strategies in primary care settings.